2013
DOI: 10.1089/acm.2012.0531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Addition ofT'ai Chito a Dietary Weight Loss Program on Lipoprotein Atherogenicity in Obese Older Women

Abstract: The addition of TC to diet education is more effective than diet education alone at improving diet quality and emerging CHD risk factors, such as LDL particle size, in obese older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 59 publications
(66 reference statements)
5
63
0
Order By: Relevance
“…Beebe et al (2013) revealed that Tai Chi exercise was associated with improvements in LDL-C particle size in obese older women. Tai Chi practicing comprises aerobic exercise and resistance exercise, increasing the whole body fat oxidation, adipose tissue lipolysis and fatty acid utilization by skeletal muscle, mobilizing lipid from adipose tissue, liver and intramuscular reserves, dictating tissue fatty acid uptake, intracellular lipid delivery and mitochondrial β-oxidation, coordinating activation of the sympathetic nervous system and induction of energy deficit-sensing pathways, promoting energy expenditure via heightened TG/FA cycling, inducing energy-sensing pathways such as adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK), activating peroxisome proliferator-activated receptor delta (PPARD)-mediated remodeling of lipid metabolism pathways in muscle, and increasing adiponectin level with strong anti-atherogenic and anti-inflammatory effects (Chang et al, 2011;Franklin et al, 2014;Gordon et al, 2014;Noland, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Beebe et al (2013) revealed that Tai Chi exercise was associated with improvements in LDL-C particle size in obese older women. Tai Chi practicing comprises aerobic exercise and resistance exercise, increasing the whole body fat oxidation, adipose tissue lipolysis and fatty acid utilization by skeletal muscle, mobilizing lipid from adipose tissue, liver and intramuscular reserves, dictating tissue fatty acid uptake, intracellular lipid delivery and mitochondrial β-oxidation, coordinating activation of the sympathetic nervous system and induction of energy deficit-sensing pathways, promoting energy expenditure via heightened TG/FA cycling, inducing energy-sensing pathways such as adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK), activating peroxisome proliferator-activated receptor delta (PPARD)-mediated remodeling of lipid metabolism pathways in muscle, and increasing adiponectin level with strong anti-atherogenic and anti-inflammatory effects (Chang et al, 2011;Franklin et al, 2014;Gordon et al, 2014;Noland, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training (RT) is a frequently used exercise modality in obese individuals and has been shown to improve muscle mass and strength, physical function, and body composition in older women [ 10 14 ]. However, RT is not considered an aerobic activity; in contrast, Tai Chi exercise is comparable to aerobic activities [ 15 , 16 ]. Aerobic activities have greater influences on obesity reduction and promote greater weight loss when compared to anaerobic activities such as RT.…”
Section: Introductionmentioning
confidence: 99%
“…The DASH diet has been shown to be an effective and reliable intervention tool in obese older adults [ 23 , 25 , 28 ]. Furthermore, the modified DASH diet (<35% fat versus <27% fat) combined with exercise results in significant decreases in fat mass and results in significant weight loss in older adults [ 15 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term “atherogenicity” which we use to refer to this phenomenon is also used in other meanings, such as blood lipid profile characteristics or characteristics of lipoproteins [1719]. Nevertheless, we continue to use the term “atherogenicity” because it has been shown that the accumulation of lipids in the arterial cells is a trigger of atherogenesis at the cellular level [7].…”
Section: Discussionmentioning
confidence: 99%